13(x+1)=x(x+1)

Simple and best practice solution for 13(x+1)=x(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(x+1)=x(x+1) equation:



13(x+1)=x(x+1)
We move all terms to the left:
13(x+1)-(x(x+1))=0
We multiply parentheses
13x-(x(x+1))+13=0
We calculate terms in parentheses: -(x(x+1)), so:
x(x+1)
We multiply parentheses
x^2+x
Back to the equation:
-(x^2+x)
We get rid of parentheses
-x^2+13x-x+13=0
We add all the numbers together, and all the variables
-1x^2+12x+13=0
a = -1; b = 12; c = +13;
Δ = b2-4ac
Δ = 122-4·(-1)·13
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{196}=14$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-14}{2*-1}=\frac{-26}{-2} =+13 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+14}{2*-1}=\frac{2}{-2} =-1 $

See similar equations:

| 5(3y-4)+4y=37 | | -9x+8=4 | | 12=0.2n | | 1.5x-4=2.5 | | -4/3x=2/15 | | -(4x-2)+12x=2(5x-1)-2(x-6)-5x | | 16=8+4y | | 3z^2+11z+10=0 | | x^2+x=648 | | 3x+2(2x-2)=9 | | -1/3(n+15)=-21 | | 4y2+8y+4=0 | | 6-x/3=1 | | X^2-5x=-x | | 8v=4v2-4 | | 4q2=-8q | | 32=x√3 | | (10/(7+(-5x))=(16/(5+7x)) | | (x+9)x=16^2 | | 8p2+7=0 | | 2+4/9x=2+x | | 5u^2+60u+100=0 | | 2z2=2z | | -19=b-9 | | Y=1.5+x2 | | (x+9)x=256 | | -100+33/(1+r)(r)=0 | | 9q2-5q=-4 | | 7x+35=-35 | | (5-v)(5v+9)=0 | | Y=2+x/0.5 | | x/3+13=21 |

Equations solver categories